Wiley Encyclopedia of Electrical and Electronics Engineering 2016
DOI: 10.1002/047134608x.w8325
|View full text |Cite
|
Sign up to set email alerts
|

Phase Change Memories: Principles and Applications

Abstract: The phase‐change memory (PCM) is a nonvolatile semiconductor technology based on thermally induced phase transitions of a thin‐film material, typically a chalcogenide. PCM relies on a resistance change to store data permanently. Although the historical origin of the PCM concept dates back to the 1970s, nowadays it is considered one of the most promising candidates for the next‐generation nonvolatile memories (NVM). In comparison with flash, PCM has the potential to improve the random access time, read throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…We continued our study by testing Ge 2 Sb 2 Te 5 , a composition repeatedly shown to be an excellent PCM memory. Figure a shows a DC- I – V curve for a Ge 2 Sb 2 Te 5 film connected to a ∼0 Ω resistor (short circuit). The plot reveals the typical behavior of a PCM: an exponential regime (characteristic of trap-limited current transport in disordered solids and chalcogenide glasses ) corresponding to the amorphous phase of the cell is followed by a sharp “snap back” at V T ≈ 1.4 V, indicating the fast crystallization of the film. Figure b shows the film crystallization and amorphization as a function of the applied voltage combining this information in a so-called resistance-voltage ( R – V characteristic).…”
Section: Results and Discussionmentioning
confidence: 99%
“…We continued our study by testing Ge 2 Sb 2 Te 5 , a composition repeatedly shown to be an excellent PCM memory. Figure a shows a DC- I – V curve for a Ge 2 Sb 2 Te 5 film connected to a ∼0 Ω resistor (short circuit). The plot reveals the typical behavior of a PCM: an exponential regime (characteristic of trap-limited current transport in disordered solids and chalcogenide glasses ) corresponding to the amorphous phase of the cell is followed by a sharp “snap back” at V T ≈ 1.4 V, indicating the fast crystallization of the film. Figure b shows the film crystallization and amorphization as a function of the applied voltage combining this information in a so-called resistance-voltage ( R – V characteristic).…”
Section: Results and Discussionmentioning
confidence: 99%
“…21 We notice from the DC-IV an exponential dependency of the subthreshold current from the applied voltage; such behavior is a sign of a charge transport mechanism dominated by field-assisted hopping as expected for amorphous chalcogenide semiconductors. 11,34 In Figure 3c, we report a time-dependent I−V measurement. The rise time of the voltage excitation was set to 100 ns to allow the detection of the threshold event (compatibly with the sampling performance of our system).…”
mentioning
confidence: 99%